2020
DOI: 10.3892/etm.2020.9233
|View full text |Cite
|
Sign up to set email alerts
|

A novel frameshift mutation in the <em>FERMT1</em> gene in a Chinese patient with Kindler syndrome

Abstract: Kindler syndrome (KS) is a rare subtype of epidermolysis bullosa that is inherited in an autosomal recessive manner with mutations in FERMT1. A number of mutations in FERMT1 have been identified in KS. The current study reported a 33-year-old Chinese man who exhibited a wide variety of clinical features, including formation of blisters, photosensitivity, cutaneous atrophy and poikiloderma, telangiectasia of the face and neck, contracture of the end limbs, nail dystrophy, muscle, eye and oral damage, tympanitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Mutations in FERMT1 (also known as KIND1), encoding the focal adhesion protein kindlin-1, cause Kindler syndrome (KS). KS patients are predominantly offspring of consanguineous couples (12) but there are exceptions (46). The major manifestation of KS is skin disorder such as atrophy, blistering, poikiloderma, photosensitivity (12,13,47).…”
Section: Fermt1 Deficiencymentioning
confidence: 99%
“…Mutations in FERMT1 (also known as KIND1), encoding the focal adhesion protein kindlin-1, cause Kindler syndrome (KS). KS patients are predominantly offspring of consanguineous couples (12) but there are exceptions (46). The major manifestation of KS is skin disorder such as atrophy, blistering, poikiloderma, photosensitivity (12,13,47).…”
Section: Fermt1 Deficiencymentioning
confidence: 99%
“…Previous studies have demonstrated that the HFD consumption, due to a lack of adequate dietary ber, causes intestinal microbial community disorders, which is a underlying reason for disturbed physiological processes and metabolic diseases, including obesity [5], hyperlipidemia and other symptoms [3,6]. Thus, how to prevent HFD-induced obesity and its complications in modern society has attracted increasing attention [7].…”
Section: Introductionmentioning
confidence: 99%